THE ROLE OF VIRTUAL REALITY THERAPY IN DENTISTRY: A BIBLIOMETRIC ANALYSIS OF CURRENT TRENDS AND APPLICATIONS - Tania Vlad; Laria-Maria Trusculescu; Ramona Amina Popovici; Andreea Sălcudean; Cristina Raluca Bodo; Sandor Csibi; Robert Nikolas Folescu; Iustin Olariu (Romanian Journal of Oral Rehabilitation)
Aim of the study: This bibliometric analysis aims to explore the current research landscape on virtual reality (VR) therapy in stomatology, identifying key publication trends, influential contributors, research themes, and potential gaps in this evolving field. Materials and methods: Using the Web of Science database, publications from 2019 to 2024 were extracted with the keywords “virtual reality” and “dentistry” resulting in 32 articles. The analysis included publication trends, leading authors, journals, collaboration networks, and thematic categorization. Results: The study found a growing interest in VR therapy, especially in the last three years, with key themes including anxiety management, dental education, clinical training, and procedural simulations. Major contributors are primarily from the USA, China, and India, with limited representation from Romania. Collaboration networks highlight the field’s interdisciplinary nature. Identified gaps include the need for standardized protocols, cost-effectiveness, and understanding long-term impacts. Conclusions: This analysis provides insights into the evolving role of VR in stomatology, emphasizing its potential benefits. Addressing challenges such as implementation costs and standardization can guide future research to optimize VR’s use in dental care.